2020
DOI: 10.1016/j.chempr.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Nanomaterials with Unconventional Phases

Abstract: Two-dimensional (2D) nanomaterials have attracted increasing interest because of their compelling physicochemical properties and promising applications. Recent studies have demonstrated that phases of nanomaterials could significantly affect their properties and applications because of the distinct atomic arrangements. Besides crystalline phases, the amorphous nanomaterials, which lack long-range atomic ordering, and heterophase nanostructures consisting of more than one phase have also shown enhanced performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 71 publications
0
93
0
Order By: Relevance
“…Phase engineering of nanomaterials has been one of the hottest research topics in recent years since the crystal phase has been proven to be one of the key factors to affect the properties and application performance of nanomaterials owing to their distinctive atomic arrangements and/or coordination modes. [16][17][18] As a representative class of materials, transition metal dichalcogenides (TMDs) have been intensively explored in the field of phase engineering of nanomaterials since they can crystallize into different crystal phases, including 2H, 1T, 1T′, and 3R phases. [19] Importantly, TMDs with different phases could exhibit distinctively different properties.…”
mentioning
confidence: 99%
“…Phase engineering of nanomaterials has been one of the hottest research topics in recent years since the crystal phase has been proven to be one of the key factors to affect the properties and application performance of nanomaterials owing to their distinctive atomic arrangements and/or coordination modes. [16][17][18] As a representative class of materials, transition metal dichalcogenides (TMDs) have been intensively explored in the field of phase engineering of nanomaterials since they can crystallize into different crystal phases, including 2H, 1T, 1T′, and 3R phases. [19] Importantly, TMDs with different phases could exhibit distinctively different properties.…”
mentioning
confidence: 99%
“…Layered 2D metal chalcogenide nanomaterials, especially transition metal dichalcogenides (TMDs), have been extensively studied in last decade owing to their intriguing physicochemical properties as well as numerous promising applications. [ 1–9 ] Recent studies have revealed that introducing a third element into binary layered 2D metal chalcogenides allows the preparation of ternary layered 2D nanomaterials, such as metal chalcogenides (e.g., Ta 2 NiS 5 and Cu 2 WS 4 ) [ 10–13 ] and metal phosphorus trichalcogenides (MPS 3 : M = Mn, Fe, Ni, Zn, etc.). [ 14–19 ] These ternary layered 2D nanomaterials normally exhibit distinct physicochemical properties and innovative applications as compared to binary 2D metal chalcogenide nanomaterials due to their unique crystal structures and versatile compositions.…”
Section: Figurementioning
confidence: 99%
“…Phase engineering of nanomaterials (PEN) [ 1 ] is attracting increasing research interest, since the crystal phases of metallic nanomaterials play an important role in determining their physicochemical properties, such as magnetic, optical, electrical, and catalytic properties. [ 2–4 ] For example, Co nanomaterials with hexagonal‐close‐packed (hcp), face‐centered‐cubic (fcc), and ε phases exhibit different magnetic properties. The hcp‐Co nanomaterials are hard magnetic materials, whereas those in fcc and ε phases are soft magnetic materials.…”
Section: Figurementioning
confidence: 99%